Breast cancer awareness among Sudanese females in Omdurman city: 2021 - Munir Rafat Munir Lawis; Mustafa Sabir (BMC, 2023)
Abstract Background Breast cancer is the most commonly diagnosed malignancy among women worldwide. In contrast to Europe, it presents generally very late in Africa. As with the rest of Africa, it is the most common primary malignancy of females in Sudan, and generally presents in stage III or IV disease. This study is intended to analyse the level of breast cancer awareness among women of Sudan. Objective To assess the level of awareness of breast cancer among Sudanese females, and their attitude towards breast changes. Also, to establish possible associations between several variables: (education level, age, contact with a breast cancer patient, residence) on awareness. Methodology A descriptive cross-sectional community-based study of 385 females in Omdurman city, selected by convenience sampling. An interview based Arabic version of Breast Cancer Awareness Measure (BCAM) was used. Data was coded and analysed using Statistical Package for Social Sciences (SPSS) v.20. Results A total of 385 females were included, of which 38.7% were 20-30 years, 47.8% were single, 53.8% had university education, 41% of them were currently unemployed, and 54.3% resided in Ummbadda's locality. When asked about the signs and risk factors of breast cancer, 55.06% and 55.8% failed to name any. The cumulative percentage of correct answers of close-ended question about signs, risk factors and Federal Ministry of Health (FMoH) screening program were 42.8%, 30.7% and 44.7% in that order. Only 38.2% knew the right method BSE, 48.2% of them rarely practiced it. 38.2% noticed a change in the breast tissue but didn't visit a doctor. The majority of them, though, said they would see a doctor if they noticed a change in the future. Conclusion There is a severe lack of awareness of breast cancer among females of the Sudanese society. Also, there was a clear ignorant attitude practiced by a significant proportion of the candidates. Recommendations Further research, to address the limitations of this study is to be done. FMoH has to improve its media massage and arrange targeted awareness campaigns.